PERAN BIMBEL IBU BANGSA DALAM MENDUKUNG KESIAPAN BERSEKOLAH ANAK USIA DINI DARI KELUARGA KURANG MAMPU SEBUAH STUDY KASUS - Brotojoyo Retnowati; Agus Santoso (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2019)
Children from poor families are facing great challenges as they are growing up. Limited resources, low-level parents’ education, and environments have given impacts on how the families raise their children and prepare them for school. This research is to find out how a school readiness program initiated by Bimbel Ibu Bangsa for children of poor families at Kampung Gunung Sari can help them to get a quality education program and also to help parents implement effective parenting styles for the success of their children. A qualitative approach with a case-study model was used. The subject of this study consisted of 4 students out of the 16 students involved in the program. The data were collected by using participatory observations, home-visit notes, field notes, voice and visual recordings, and also by interviewing the parents and teachers. The validity of data was determined by triangulating and member-checking the data. The results of this research indicate that this program is quite able to be held with low budgets and will still be able to give quality education if the program is supported by the stakeholders in the community. The results also show that children and parents enrolled in this program gain many benefits shown by their adaptive parenting styles and children’s modified behaviours for the upcoming school readiness and overall better quality of life.